China's proposing behavior in Global Governance: the cases of the WTO Doha Round negotiation and G-20 process - Hongsong Liu (Revista Brasileira de Política Internacional, 2014)
This article examines China's proposals on the reform of global governance, and discusses the main features of China's proposing behavior in the cases of the WTO Doha Round negotiation and G-20 Process. The main findings are: (1) in the critical junctures of global governance reform, China engaged the reform of the global governance institutions proactively, and put forward a series of reform proposals; (2) in proposing behavior, China argued the global governance institutions should be properly adjusted without intention to change the basic principles, refrained from playing a leadership role while proposing jointly with other countries, and upheld the principled idea of pro-development.